Genotype sensitivity and adaptability for fruit yield in red and green okra on environmental change - SHAHRIZAL M. ABDILLAH; MUHAMAD SYUKUR; WILLY B. SUWARNO; ARYA W. RITONGA; ANUNG WAHYUDI (Society for Indonesian Biodiversity, 2023)
Abstract. Abdillah SM, Syukur M, Suwarno WB, Ritonga AW, Wahyudi A. 2023. Genotype sensitivity and adaptability for fruit yield in red and green okra on environmental change. Biodiversitas 24: 4289-4298. Okra is vegetable plant consumed in immature and beneficial plants of various health. For breeders, this crop had a big chance to develop a high-yield genotype in various conditions. To develop a new variety must be known adaptability and stability in environment tests. This research aimed to evaluate the fruit yield response, sensitivity, and adaptability of okra genotypes in four environment trials. A randomized complete block design with three replications was used in each environment, with ten okra genotypes as the treatment. The AMMI-1, AMMI-2 and GGE biplot was used to illustrate genotype stability and their adaptability. Genotype by environment interaction significantly affected fruit yield, with the environment having a large contribution, with SWR01 being the highest yield. The rate of rainfall and PC1 were explained as 36.98% and 70.17% to the GEI sum of squares, respectively. ‘ZAHIRA’ and ‘GSO03’ showed sensitivities to the rate of rainfall. Genotypes ‘SWR01’ and ‘GSO03’ were the most favorable genotype according to ASV and yield performance across environments The AMMI-1, AMMI-2 and GGE biplot confirmed that both were the most suitable genotype for developing a recent variety of okra in a wide environment.